Tillage intensity reductions when combined with yield increases may slow soil carbon saturation in the central United States - Deepak R. Joshi; David E. Clay; Ron Alverson; Sharon A. Clay; Shaina Westhoff; Jane M. F. Johnson; Tong Wang; Heidi Sieverding (Scientific Reports)
Abstract Tillage intensity reduction when coupled with higher yields and better equipment, has increased the potential to sequester carbon in farm fields. However, a few experiments have demonstrated that this is occurring. This studies objective was to investigate the macro-scale effects of crop tillage intensity decreases and yield increases and on soil organic carbon (SOC) storage in Nebraska (NE), Iowa (IA), Minnesota (MN), and South Dakota (SD) from 2000 to 2021. The analysis was based on grower surveys, state yields from 2000 to 2021, and over 12 million surface soil samples that were aggregated by state and year. The model used first order kinetics, and it consisted of three pools [non-harvested carbon (NHC), SOC, and atmospheric carbon dioxide (CO2)]. Annual NHC additions were estimated from the state-level crop yields and tillage intensity reductions were estimated from producer surveys. Across the four states and 21 years, there was an estimated decrease of 0.0339 soil mixing events per year, corn (Zea mays) and soybean (Glycine max) yields increased by 63 and 38%, respectively, and SOC increased at a rate of > 460 kg SOC-C/(ha × year). In addition, strong (p < 0.01) linear correlations between NHC additions and SOC gains indicate that soil at the state-scale soil was not approaching carbon saturation.